Illumination Brush: Interactive Design of Image-based Lighting - Okabe, Makoto; Matsushita, Yasuyuki; Igarashi, Takeo; Shum, Heung-Yeung (Microsoft, 2006)
To help artists design customized lighting environments, we present a simple user interface for designing image-based lighting. Our system allows the artist to directly specify the appearance of the resulting image by painting and dragging operations. Our system constructs an image-based lighting model that produces the desired (and painted) appearance by solving the inverse shading problem. To obtain realistic lighting effects, we design diffuse and specular lighting effects separately. We represent diffuse lighting using low frequency spherical harmonics and pre-computed radiance transfer. For specular lighting, we simply project the painted highlights onto a cube map texture. We also provide an interface with which the artist can drag highlights and shadows on the surface to control the orientation of the entire lighting environment. We demonstrate that our technique is useful and practical for adding lighting effects to synthetic objects. We also show an application of seamlessly merging synthetic objects into photographs.